2004
DOI: 10.1024/1010-0652.18.34.157
|View full text |Cite
|
Sign up to set email alerts
|

Zur Fremdeinschätzung von Schülerselbstkonzepten durch Lehrer und Mitschüler

Abstract: Zusammenfassung: Das “Internal/External Frame of Reference Modell” (I/E-Modell) von Marsh (1986) postuliert, dass zur Ausbildung fachspezifischer Selbstkonzepte neben sozialen Vergleichen (externaler Bezugsrahmen) auch dimensionale Vergleiche (internaler Bezugsrahmen) herangezogen werden. Dimensionale Vergleiche sind Vergleiche der eigenen Leistungen in zwei Domänen. In der vorliegenden Untersuchung wurde geprüft, ob das I/E-Modell auch für fremdeingeschätzte Selbstkonzepte gilt. Dazu wurden die mathematischen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
2
19
2
4
Order By: Relevance
“…Furthermore, as predicted by Marsh and Ayotte's (2003) differential distinctiveness hypothesis, weaker between-domain relations (i.e., greater domain-specificity) were also found for older students for both homework and classroom emotions. In contrast to teachers' tendency to view students' attributes as habitual and domain-general in nature (Marsh, 1993;Marsh, Smith, & Barnes, 1983;Pohlmann, Moeller, & Streblow, 2004), these results thus suggest that it is more appropriate for educators to view students' academic emotions, especially those of older students, as linked to specific subjects in both the classroom setting (e.g., enjoyment of math classes) as well as homework situations (e.g., enjoyment of math homework). …”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, as predicted by Marsh and Ayotte's (2003) differential distinctiveness hypothesis, weaker between-domain relations (i.e., greater domain-specificity) were also found for older students for both homework and classroom emotions. In contrast to teachers' tendency to view students' attributes as habitual and domain-general in nature (Marsh, 1993;Marsh, Smith, & Barnes, 1983;Pohlmann, Moeller, & Streblow, 2004), these results thus suggest that it is more appropriate for educators to view students' academic emotions, especially those of older students, as linked to specific subjects in both the classroom setting (e.g., enjoyment of math classes) as well as homework situations (e.g., enjoyment of math homework). …”
Section: Discussioncontrasting
confidence: 58%
“…This finding stands in contrast to several studies indicating that teachers tend to view individual students' characteristics as habitual, domain-general attributes and not as domain-specific phenomena (see Marsh, 1993;Marsh, Smith, & Barnes, 1983;Pohlmann, Moller, & Streblow, 2004). Thus, one can assume that false judgments are often made by teachers with regard to the emotional experiences of their students in different domains.…”
Section: Discussioncontrasting
confidence: 51%
“…To enhance the eVectiveness of instruction (e.g., by adapting teaching to individual diVerences; cf., Snow & Swanson, 1992), educators should be made aware of the domain speciWcity of students' emotional experiences. Previous studies have shown that teachers tend to perceive individual student characteristics as habitual, domain-transcending attributes (cf., Marsh, 1993;Pohlmann, Möller, & Streblow, 2004). In view of our Wndings on the domain-speciWc organization of academic enjoyment, it can be assumed that teachers' domain-general conceptions can lead to false inferences regarding the emotions experienced by individual students in diVerent domains.…”
Section: Discussionmentioning
confidence: 99%